Cellular Features Revealed by Transverse Laser Modes in Frequency Domain (Adv. Sci. 1/2022). Issue 1 (5th January 2022) - Qiao, Zhen; Xu, Hongmei; Zhang, Na; Gong, Xuerui; Gong, Chaoyang; Yang, Guang; Chew, Sing Yian; Huang, Changjin; Chen, Yu‐Cheng
Abstract : Transverse Laser Modes In article number 2103550 by Changjin Huang, Yu‐Cheng Chen, and co‐workers, the key mechanism governing the frequency distributions of transverse modes in single cell biological lasers are revealed. The cover art illustrates the concept of distinctive laser fingerprints generated by cells, which could be employed to provide cellular information. Morphological information of cells could be interpreted through hyperspectral imaging of laser modes. Applications including cell classification and monitoring of cell adhesion are explored and demonstrated.